Coastal Yorubaland: Habitability, Inhabitance, and Inheritances - Toyin Falola (Yoruba Studies Review)
Although the conference from which this Special Issue derives was convened by two prominent historians, this article is multi-disciplinary; both within and outside the boundaries of history. The purpose is to merge various ideas in different disciplines to argue that the study of Coastal Yorubaland as an important unit of analysis should, on the one hand, stand alone, and, on the other, be integrated into larger studies in all fields from Art to Zoology. For thousands of years, people have been living along the coast, experiencing interactions with the sea: they were shaped by the lagoon and sea, and they in turn shaped the coastline and waterways. The past of the coastal Yoruba people shapes their present, and this present will shape their future. In this article, I speak to the impact of the consciousness of history, the consciousness of the past, and the consciousness of self and identity on coastal Yorubaland.